Kavalactones, A Novel Class of Protein Glycation and Lipid Peroxidation Inhibitors - Upadhyay, Atul; Tuenter, Emmy; Ahmad, Rizwan; Amin, Adnan; Exarchou, Vasiliki; Apers, Sandra; Hermans, Nina; Pieters, Luc (Planta Medica, 2014)
Both advanced glycation endproducts and advanced lipoxidation endproducts are implicated in many age-related chronic diseases and in protein ageing. In this study, kawain, methysticin, and dihydromethysticin, all belonging to the group of kavalactones, were identified as advanced glycation endproduct inhibitors. With IC50 values of 43.5 ± 1.2 µM and 45.0 ± 1.3 µM for kawain and methysticin, respectively, the compounds inhibited the in vitro protein glycation significantly better than aminoguanidine (IC50 = 231.0 ± 11.5 µM; p = 0.01), an established reference compound. Kawain and methysticin also inhibited the formation of dicarbonyl compounds, which are intermediates in the process of advanced glycation endproduct formation. Similarly, kawain and aminoguanidine prevented the formation of thiobarbituric reactive substances in both low-density lipoprotein and linoleic acid oxidation. Moreover, kawain and aminoguanidine prevented advanced glycation endproduct formation by chelating Fe3+ and Cu2+ two to three times better than aminoguanidine. Furthermore, kawain increased the mean life span of Caenorhabditis elegans exposed to high glucose. With glycation inhibiting, lipid peroxidation inhibiting, metal chelating properties, and life span extending ability, kavalactones show a high potential as advanced glycation endproducts and advanced lipoxidation endproduct inhibitors.
Keywords: advanced glycation endproducts (AGEs); advanced lipoxidation endproducts (ALEs) kavalactones; kawain; chelation; Caenorhabditis elegans